Free access to scholarly e-books and articles?: Thank you, but no, thank you - Bonnin, Juan Eduardo (2020)
Academic publishers have begun to offer free access to their content. They present this action both as a positive response to global quarantine measures and as an active response to COVID-19 research. What is the reason for this unexpected generosity? Did publishers suddenly realize that scientific knowledge should benefit everyone, and not be used commercially to make a profit? Did they recognize that they have an immoral business model which relies on the work done for free by thousands of scientist around the world who write and review for them? Did governments realize how stupid it is to fund scientific research with public money and then pay again to access the results of that very same public-funded research? I offer here a hypothesis: publishers are afraid that, ultimately, scientists will inevitably realize that they are unnecessary and both third and first world scholars would resource to alternative sources of knowledge, mainly, academic pirate sites such as Sci-Hub and Libgen.